Uniform Surface Modification of 3D Bioglass®-Based Scaffolds with Mesoporous Silica Particles (MCM-41) for Enhancing Drug Delivery Capability - Boccardi, Elena; Philippart, Anahí; Juhasz-Bortuzzo, Judith A.; Beltrán, Ana M.; Novajra, Giorgia; Vitale-Brovarone, Chiara; Spiecker, Erdmann; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2015)
The design and characterization of a new family of multifunctional scaffolds based on bioactive glass (BG) of 45S5 composition for bone tissue engineering and drug delivery applications is presented. These BG-based scaffolds are developed via a replication method of polyurethane packaging foam. In order to increase the therapeutic functionality, the scaffolds were coated with mesoporous silica particles (MCM-41), which act as an in-situ drug delivery system. These sub-micron spheres are characterized by large surface area and pore volume with a narrow pore diameter distribution. The solution used for the synthesis of the silica mesoporous particles was designed to obtain at the same time a high ordered mesoporous structure and spherical shape, both are key factors for achieving the desired controlled drug release. The MCM-41 particles were synthesized directly inside the BG-based scaffolds and the drug release capability of this combined system was evaluated. Moreover the effect of MCM-41 particle coating on the bioactivity of the BG-based scaffolds was assessed. The results indicate that it is possible to obtain a multifunctional scaffold system characterized by high and interconnected porosity, high bioactivity and sustained drug delivery capability.